Peran Katekese Digital Sebagai Media Pembinaan Iman Kaum Muda Kristiani - Andreas Jimmy; Bernard Antonius Rahawarin; Sandi Nugroho (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2023)
This article highlights the important role of catechism in developing the faith of young Catholics in the modern era. This study uses a theological analytical discourse methodology to analyze the role of catechism as a medium for building faith. Catechesis is a means used by the Church to communicate the teachings of faith to the people. Through catechesis, the Church can provide effective accompaniment of faith to young people. This study focuses on the problems faced by young people today. They are the next generation of the Church who need special attention because they are very vulnerable to being influenced by the fast and swift currents of modernity. Therefore, an effective assistance effort is needed for them. The research findings show that young people, who are in a period of searching for identity, tend to get bored easily and are quickly satisfied. In this context, catechesis as a form of faith formation is an effective choice and responsive to the lifestyle of today's youth. Through catechesis, young people can gain a deeper understanding of the teachings of the faith, strengthen their relationship with God and develop a strong Christian identity. Digital catechesis, which combines technology with messages of faith, can be a relevant and attractive medium for young people. In conclusion, digital catechesis has a significant role in developing the faith of young Christians. In facing the challenges of modern times, the Church needs to use catechesis as an effective strategy to assist young people in strengthening their faith. By utilizing technology and adapting the right content, digital catechism can be an effective tool in forming a young generation who are firm in their faith and ready to face the changing times.